Persepsi Wisatawan Muslim terhadap Destinasi Wisata Ramah Muslim yang Belum Bersertifikasi Halal: (Studi pada Wisata Sikabung Kabung, Kabupaten Deli Serdang) - Parlindungan Parlindungan; Syamsul Effendi; Tuti Alawiyah (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study aims to analyze Muslim tourists’ perceptions of Muslim-friendly tourism destinations that have not yet obtained halal certification, focusing on the aspects of trust, safety, and comfort. The research employs a qualitative descriptive approach and was conducted at Sikabung Kabung Tourism Site in Deli Serdang Regency. Data were collected through in-depth interviews, observation, documentation, and literature study, and analyzed using an interactive analysis technique consisting of data reduction, data display, and conclusion drawing. The findings indicate that Muslim tourists’ perceptions tend to be positive despite the absence of halal certification. Trust is primarily formed through direct experiences with facilities and environments that support Islamic values, although some doubts remain regarding the halal status of food and beverages. The sense of safety is perceived both physically and psychologically due to a conducive environment aligned with Islamic norms. Meanwhile, comfort is influenced by the availability of basic facilities and the compatibility between expectations and actual conditions. This study concludes that the implementation of Muslim-friendly tourism can provide a positive experience for tourists; however, halal certification remains essential as a formal assurance to enhance trust, safety, and comfort sustainably.